Faktor Eksternal Petani terhadap Penggunaan Pupuk Ireng-Ireng di Kecamatan Wuluhan Kabupaten Jember - Purwandhini, Ari Septianingtyas; Pudjiastutik, Endang Wahyu; Kurniawan, Deddy (Program Studi Agribisnis, 2025)
This study aims to analyze external factors influencing farmers’ responses to the use of Ireng-ireng fertilizer in rice farming in Wuluhan District, Jember Regency. Three external indicators were examined: expected benefits, time required to obtain benefits, and the magnitude of sacrifices incurred. Primary data were collected from 80 farmers and analyzed using Likert-scale tabulation. The results show that 81% of farmers perceived significant benefits, 50% stated that the benefits appeared within a similar time frame as other fertilizers, and 89% considered the sacrifices incurred to be proportional or lower than the benefits gained. These findings indicate that Ireng-ireng fertilizer is perceived as efficient, feasible, and compatible with farmers’ cultivation practices, thus supporting its potential acceptance and sustainable use.